Large‐scale maps of variable infection efficiencies in aquatic Bacteroidetes phage‐host model systems. (27th June 2016) - Holmfeldt, Karin; Solonenko, Natalie; Howard‐Varona, Cristina; Moreno, Mario; Malmstrom, Rex R.; Blow, Matthew J.; Sullivan, Matthew B.
Summary: Microbes drive ecosystem functioning and their viruses modulate these impacts through mortality, gene transfer and metabolic reprogramming. Despite the importance of virus‐host interactions and likely variable infection efficiencies of individual phages across hosts, such variability is seldom quantified. Here, we quantify infection efficiencies of 38 phages against 19 host strains in aquatic Cellulophaga ( Bacteroidetes ) phage‐host model systems. Binary data revealed that some phages infected only one strain while others infected 17, whereas quantitative data revealed that efficiency of infection could vary 10 orders of magnitude, even among phages within one population. This provides a baseline for understanding and modeling intrapopulation host range variation. Genera specific host ranges were also informative. For example, the Cellulophaga Microviridae, showed a markedly broader intra‐species host range than previously observed in Escherichia coli systems. Further, one phage genus, Cba41, was examined to investigate nonheritable changes in plating efficiency and burst size that depended on which host strain it most recently infected. While consistent with host modification of phage DNA, no differences in nucleotide sequence or DNA modifications were detected, leaving the observation repeatable, but the mechanism unresolved. Overall, this study highlights the importance of quantitatively considering replication variations in studies of phage–host interactions.